Propriedades de recobrimento de ligações químicas em mecanismos de reações orgânicas Sn2 - Mendonça, José Gutembergue de (2019)
Organic Sn2 reactions are enough studied, because they are the basis for organic synthesis and biochemical processes. The reactions with halomethanes , where we have the X ' ⋯ CH3X where x = F, Cl and Br and X = Cl has been the focus of much experimental and theoretical study, over the years. Given this, this work has as objective the application of method based on analysis of coating properties of chemical bonds to the study of the situation of the chemical bonds in the course of the reaction mechanisms where you can reveal important aspects of chemical reactions, such as: the Covalent character, Electron density, among other trends. Nevertheless, this work has as its main objective the application of coating model for the study of chemical bonding in SN2 reaction mechanism. In this sense, it is intended to monitor the change of the properties of covering in the course of the reaction coordinate. SN2 reactions discussed in this work were chosen because they are well known and already known, allowing for a more in-depth understanding of the properties of covering. The methodology used involved calculations based on DFT with B3LYP functional, for the calculation of the transition and to the IRC calculation (Intrinsic Reaction Coordinate), both for the direct reaction as functional and inverse wB97X-D, which features of correction long range and dispersion and localization of orbitals method employed was the Pipek-Mezey. The combinations used for the mechanism is by varying the nucleophile (Lewis bases) halogenated: F, Cl and Br, attacking the methane chlorine with an angle of 180° with respect to the Group-leaver. Notable results obtained with respect to carbon connections/halogen polarizability, as if formed these αOP values, connection for qop and ,, increased proportionately with the Lewis base strength, giving a tendency of the method as for the covalent radius of the link formed. This way to the theoretical understanding of chemical bonds along the reaction coordinate, the model features a sensitivity on ChemBOS as to determination of Covalent character.